The impact of COVID-19 lockdown announcements on mental health: quasi-natural experiment in Lombardy, Italy. (12th April 2022) - Wang, Yuxi; Lugo, Alessandra; Amerio, Andrea; Cavalieri d'Oro, Luca; Iacoviello, Licia; Odone, Anna; Zucchi, Alberto; Gallus, Silvano; Stuckler, David; ,
Abstract: Background: Evidence showed that mental health problems have risen markedly during COVID-19. It is unclear if part of the mental sufferings relates to the climate of uncertainty and confusion originated from rough communication by health officials and politicians. Here, we test the impact of unanticipated policy announcements of lockdown policies on mental health of the older population. Methods: We used a representative telephone-based survey of 4400 people aged 65 years or older in Italy's Lombardy region to compare information on self-reported symptoms of anxiety, depression and poor-quality sleep of subjects interviewed on the days of the policy announcement with that of subjects interviewed on other days. We used regression models adjusting for potential socio-demographic confounders as well study design with inverse probability weighting. Results: On days when policymakers announced to extend the lockdown, mental health deteriorated on average by 5.5 percentage points [95% confidence interval (CI): 1.1–9.8] for self-reported anxiety symptoms and 5.1 percentage points (95% CI: 2.7–7.4) for self-reported depressive symptoms. The effect of the announcement to shorten the lockdown is more moderate but statistically significant. These associations were short term in duration; after just 1 day, self-reported mental health and sleep quality return to levels better than pre-announcement until a new policy change. Conclusions: Our research shows that lockdown policy announcements are associated with short-term worsening in mental distress, highlighting the importance of appropriate communication strategies and political determinations in crisis times.